Estudio de viabilidad para la creación de la empresa de asesorías administrativas y financieras para Mipymes comercializadoras y distribuidoras de electrodomésticos de la ciudad de Pereira 2013-2104 (2014)
This study is focused on creating a company able to offer financial and administrative advisory to small and medium enterprises dealing and distributing home appliances in the city of Pereira. Besides, that compromises itself on the region´s economic growth, involving human talent that goes to reducing unemployment. The company´s creation obeys to the existing necessity of the appliances market to count with suitable people able to offer advice, in order to accomplish different processes such as constitution, administration and financing, as well as facing the local market´s competition and illegality of this type of business, with the aim of achieving sustainability in the short and medium term. LAM Advisors S.A.S borns with the purpose of meeting the satisfaction of small and medium enterprises needs dealing and distributing home appliances, for which it started with the project’s feasibility awareness and viability to start, understanding that marketing, technical, legal, administrative and financial studies were already made, which detail the opportunity, convenience and possibility of the company´s creation and strengthening, as well as meting the planned aims, through a vision and mission clearly defined.